The Influence of Self-Reward and Peer Support on Personal Financial Management of Generation Z with Financial Literacy as an Intervening Variable - Alya Rahayu; Jurana, Jurana; Andi Mattulada; Rahma Masdar (Lembaga Riset Ilmiah, 2025)
Personal financial management is an important skill that individuals must have, especially Generation Z students who are faced with financial and social challenges. This study aims to analyze the effect of self-reward and peers on personal financial management with financial literacy as an intervening variable. The population in this study were students of the Accounting Study Program at Tadulako University with a sample of 89 respondents determined using proportional stratified random sampling technique. Data collection was carried out through questionnaires and analyzed using the SEM-PLS method with the SmartPLS 4.0 application. The results showed that self-reward and peers have a significant effect on financial literacy and personal financial management. Self-reward and peers affect personal financial management through financial literacy as an intervening variable (partial mediation).